Shelf-life Prediction of Canned Pacri Nanas Using the Accelerated Shelf-life Test (ASLT) Method - Maherawati, Maherawati; Rahayuni, Tri; Hartanti, Lucky (Department of Agro-industrial Technology, University of Brawijaya, 2024)
AbstractPacri nanas is a traditional Malay food made from fresh pineapple cooked with various herbs/spices and coconut milk. Pacri nanas can be marketed more widely if packed in cans. This study aims to estimate the shelf-life of canned pacri nanas using the Accelerated Shelf-Life Test (ASLT) method. The storage temperatures used in this study were 35 °C, 45 °C, and 55 °C. The parameters observed were sensory characteristics: color, aroma, taste, texture, and overall appearance. The results showed that all parameters decreased during storage, as indicated by the negative slope graph. The first-order reaction affects the sensory parameters decrease during storage. The lowest activation energy (Ea) value used to determine the product shelf-life is the aroma parameter with the regression equation y = -2416.4x + 5.9911, so the resulting activation energy is 4798.97 cal/mol. The shelf-life of pacri nanas at storage temperatures of 35 °C, 45 °C, and 55 °C were 11.3, 8.8, and 7.0 months, respectively. Storage of canned pacri nanas is recommended at room temperature (30 °C) with an estimated shelf-life of 12.8 months.Keywords: pineapple, storage life, traditional food AbstrakPacri nanas adalah makanan tradisional Melayu yang terbuat dari nanas segar yang dimasak dengan berbagai bumbu/rempah dan santan. Pacri nanas bisa dipasarkan lebih luas jika dikemas dalam kaleng. Penelitian ini bertujuan untuk memperkirakan umur simpan dengan metode Accelerated Shelf-Life Test (ASLT) pada pacri nanas yang dikemas dalam kaleng. Suhu penyimpanan pacri nanas tersebut pada penelitian ini adalah 35 °C, 45 °C, dan 55 °C. Parameter yang diamati adalah karakteristik sensorik, yaitu warna, aroma, rasa, tekstur, dan kenampakan secara keseluruhan. Hasil penelitian menunjukkan bahwa seluruh parameter mengalami penurunan selama penyimpanan yang ditunjukkan dengan grafik dengan kemiringan negatif. Reaksi yang memengaruhi penurunan parameter sensorik selama penyimpanan merupakan reaksi orde pertama. Nilai energi aktivasi (Ea) terkecil yang digunakan untuk menentukan umur simpan produk adalah parameter aroma dengan persamaan regresi y = -2416,4x + 5,9911 sehingga energi aktivasi yang dihasilkan adalah 4798,97 kal/mol. Umur simpan pacri nanas pada suhu penyimpanan 35 °C, 45 °C, dan 55 °C masing-masing adalah 11,3, 8,8, dan 7,0 bulan. Penyimpanan pacri nanas yang dikemas dalam kaleng dianjurkan pada suhu ruangan (30 °C) dengan perkiraan umur simpan 12,8 bulan.Kata kunci: makanan tradisional, nanas, waktu penyimpanan